GOOD CORPORATE GOVERNANCE MODERATES THE RELATIONSHIP BETWEEN GREEN ACCOUNTING AND FINANCIAL PERFORMANCE - Fina Fitriyana; Tati Rosyati (Universitas La Tansa Mashiro, 2026)
This study aims to experimentally ascertain and demonstrate the impact of Good Corporate Governance, as proxied by the Board of Directors and Audit Committee, moderating Green Accounting Variables on company performance assessed by EVA with moderating variables related to intellectual capital. During 2018–2022, consumer cyclical businesses in the industrial sector were listed on the Indonesia Stock Exchange. Quantitative research with an associative approach was the methodology used. Purposive sampling was the method used to generate a sample of fifty data points. Secondary data from the annual reports of state-owned enterprises for 2018–2022 were obtained using a documentation approach. Using Eviews 9 software, the analysis techniques used included descriptive statistical analysis, panel data regression analysis, classical assumption tests, MRA tests, t and F statistical tests, and coefficient of determination. The findings indicate that (1) the relationship between variable x (Good Corporate Governance) and variable y (EVA) is significantly moderated by the moderating variable. The Adjusted R-squared value of 0.99 indicates that, with moderation, the impact of variable x, which initially had an influence of 27% (before the moderating variable), becomes very strong at 99%.